Milking the environment: Ensuring sustainable use of water and land resources in dairy systems - Bosire, Caroline K.; Kang'ethe, Edwin; Rao, E.J.O.; Wijk, Mark T. van (International Livestock Research Institute, 2021)
The water and land footprints allow us to answer a broad range of questions in agriculture. In dairy production, knowing how improvements in milk production affect water or land resources use and how to ensure that producing milk on farms does not deplete these resources is important for sustainability.